Pull-off bond behavior of anchored random-chopped FRP composites bonded to concrete. (1st February 2018) - Wang, Zhen; Khalid, Hammad R.; Seo, J.H.; Kang, Jingfu; Lee, H.K.
Abstract: An externally bonded random-chopped FRP composite can efficiently strengthen concrete structures, though premature debonding is commonly reported, which can be prevented using an anchorage system. In this paper, the pull-off bond strength of anchored random-chopped FRP composites bonded to concrete was tested by direct pull-off tests. The effects of different parameters, in this case the anchorage depth, the diameter of the FRP anchors, and the concrete compressive strength levels were investigated. Finally, analytical models from the literature were used to predict the pull-off bond behavior of the samples. The test results revealed that the FRP anchors efficiently prevented cohesive failures of random-chopped FRP composites-to-concrete bonded samples and significantly increased their pull-off bond strength compared to unanchored control samples. The prediction results of the pull-off bond behavior according to Kim and Smith's model were in good agreement with the experimental data.